2017
DOI: 10.1103/physrevd.96.044020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical binary black hole mergers in dynamical Chern-Simons gravity: Scalar field

Abstract: Testing general relativity in the nonlinear, dynamical, strong-field regime of gravity is one of the major goals of gravitational wave astrophysics. Performing precision tests of general relativity (GR) requires numerical inspiral, merger, and ringdown waveforms for binary black hole (BBH) systems in theories beyond GR. Currently, GR and scalar-tensor gravity are the only theories amenable to numerical simulations. In this article, we present a well-posed perturbation scheme for numerically integrating beyond-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(165 citation statements)
references
References 70 publications
2
163
0
Order By: Relevance
“…The GR BBH background is evolved using a well-posed generalized harmonic formalism, with details given in [22][23][24][25]. The first-order scalar field is evolved using the formalism detailed in [11]. Finally, the metric perturbation is evolved using the formalism given in [13], a well-posed perturbed analogue of the generalized harmonic formalism.…”
Section: B Evolutionmentioning
confidence: 99%
See 3 more Smart Citations
“…The GR BBH background is evolved using a well-posed generalized harmonic formalism, with details given in [22][23][24][25]. The first-order scalar field is evolved using the formalism detailed in [11]. Finally, the metric perturbation is evolved using the formalism given in [13], a well-posed perturbed analogue of the generalized harmonic formalism.…”
Section: B Evolutionmentioning
confidence: 99%
“…We give details on perturbed gauge choices in Appendix B. We use the boundary conditions detailed in [11,13,26,27].…”
Section: B Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, since it leads to equations of motion with higher-order derivatives, it is expected to contain Ostrogradsky modes if treated as a complete theory (i.e., not as a perturbative expansion). For the so-called dynamical Chern-Simons gravity (where also an explicit kinetic term for ϕ is present), the authors of [36] showed that there is at least a ghost instability above a certain momentum cutoff and the authors of [37] provided evidence that the theory does not admit a well-posed initial value formulation (see also [38] for numerical simulations using the perturbative approach). However, to the best of our knowledge, a proper canonical analysis of this theory has never been performed in order to count the number of DOF at the nonlinear level.…”
Section: F ðPþ: Chern-simons Gravitymentioning
confidence: 99%